2015
DOI: 10.1103/physreva.91.052328
|View full text |Cite
|
Sign up to set email alerts
|

Quantum computation with noisy operations

Abstract: In this paper, we show how to use low-fidelity operations to control the dynamics of quantum systems. Noisy operations usually drive a system to evolve into a mixed state and damage the coherence. Sometimes frequent noisy operations result in the coherent evolution of a subsystem, and the dynamics of the subsystem is controlled by tuning noisy operations. Based on this, we find that universal quantum computation can be carried out by low-fidelity (fidelity < 90%) operations.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 36 publications
(44 reference statements)
0
4
0
Order By: Relevance
“…The resonance line of W 13+ has tentatively been identified in spectra measured at Berlin-EBIT [7,8]. However, we exclude the data from the present comparison because the identification in [7,8] is controversial [17,20]. Kobayashi et al [15] reported that the corresponding line was not observed in the predicted region measured by…”
Section: Resultsmentioning
confidence: 82%
See 1 more Smart Citation
“…The resonance line of W 13+ has tentatively been identified in spectra measured at Berlin-EBIT [7,8]. However, we exclude the data from the present comparison because the identification in [7,8] is controversial [17,20]. Kobayashi et al [15] reported that the corresponding line was not observed in the predicted region measured by…”
Section: Resultsmentioning
confidence: 82%
“…While they observed weak resonance lines in the spectra except for tungsten, the emission spectra for all of the elements they studied are dominated by the transitions. Li et al [17] assigned other Pm-like lines prominent in tungsten spectra measured by high-temperature superconducting EBIT (SH-HtscEBIT) to and transitions. However, the assignment is inconsistent with that by Kobayashi et al [16].…”
Section: Manuscriptmentioning
confidence: 99%
“…In particularly, the QAP can be used to decrease the weigh of vacuum state component in nonlocal mixed hyperentangled state and increase the quality of nonlocal hyperentangled photon system. [56,57] Hyperentanglement concentration protocol (hyper-ECP) [58][59][60][61] and hyperentanglement purification protocol (hyper-EPP) [62][63][64][65] have been used to distill high-quality nonlocal hyperentangled photon systems from a set of nonlocal photon systems in partially hyperentangled pure state and mixed hyperentangled state (composite of maximally hyperentangled states), respectively.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, quantum computing has attracted many interests [1][2][3][4], and is considered to be superior to classical computation in solving many practical problems, such as factoring large integers [5] and searching unsorted databases [6]. Quantum logic gates are the key component to put quantum computing into practice.…”
Section: Introductionmentioning
confidence: 99%